Mother's Knowledge and Attitude About Handwashing With Soap With Toddler Diarrhea in Sugihwaras Village - Ferdiansyah, Nafilah Maulana; Muhammad Afif Hilmi; Rodiah, Dina (Prodi keperawatan sidoarjo, politeknik kesehatan kemenkes surabaya indonesia, 2024)
Handwashing with soap (CTPS) is a healthy behavior that has been scientifically proven to prevent the spread of infectious diseases such as diarrhea. The purpose of this study is to know the picture of knowledge and attitudes of toddler mothers about handwashing with soap (CTPS) with the incidence of diarrhea in toddlers. The case study research design is descriptive with a case study approach whose population is mothers who have toddlers affected by diarrhea in Sughwaras Candi Village, Sidoarjo. Based on the results of the study, 17 (52%) respondents are well informed, and 16 (48%) respondents are knowledgeable enough about CTPS. 3 (9%) respondents were positive and 30 (90%) respondents were negative about CTPS. 25 (76%) toddlers have acute diarrhea and 8 (24%) toddlers develop chronic diarrhea. The results of the study above showed that mothers of toddlers have a dominant good knowledge about CTPS, have a dominant negative attitude about CTPS, and most of the dominant toddlers affected by acute diarrhea.